The Existing State Analysis of Working Children on the Street in Sanliurfa, Turkey - Selma KAHRAMAN; Hülya KARATAŞ (Tehran University of Medical Sciences, 2018)
Background: we aimed to determine the existing state analysis of children on the street and also attending to a school. The children's ages were between 13-18 yr, attending grades between 7-12th grade. Methods: The sample group was 54,928 students in Sanliurfa, Turkey. The data were analyzed using Chi-square test (P<0.05). Results: 82.8% of working children were male. 92.5% were elder than 12 yr old and 85.8 % had more than 4 siblings. 52.7% of the families' income was less than 1,000 TL per month. 79.9% of the children had worked in different places before. The distribution of working places was 66.4% in an establishment, 9.5% in the fields, 7.5% in the bazaar and in the streets, 2.8% in bus terminal, 2.9% in industry, 2.5% in parks. The 46.3% of the children stated that they are working willingly. 50.7% were working 6 to 10 h a day. 64.4% were giving the money they earned to their families. 82.1% of the children stated that they liked to attend the school but 62.8% sometimes did not go to school. 20.6% went to work instead of school in those days. The 62.2% of the children answered the question; "According to you, should the children work?" with;"No". Conclusion: The children started working at very early ages and they faced unfavorable situations. To avoid the children work in very early ages, it is suggested to make educational programs and to compose policies to resolve the problems that force the children to go to work.